PENERAPAN INFORMASI AKUNTANSI DIFERENSIAL DALAM PENGAMBILAN KEPUTUSAN MEMBELI ATAU MEMBUAT SENDIRI PRODUK SETENGAH JADI PADA UD. BERKAT ANUGERAH - Tampubolon, Phamela D; Saerang, David Paul Elia; Poputra, Agus Toni (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Amid competition is so rapid and uncertain economic conditions, every company is required to be more efficient in order tobe more efficient in orderto survive and all of it can not be separated from the role of management.Â  Management measure which is occupied to measure the success or failure of the company is profit. To produce an efficient profit differential accounting information requires management to select the best course of action among alternatives available. The purpose of this study is to analyze the application of differential accounting information in the decision to buy or make your own semi-finished products on UD. Berkat Anugerah. This study uses a descriptive research method. The result of the analysis of research conducted on UD. Berkat Anugerah seen from the cost accounting showed diferential role in the short-term decision making, where the company should buy semi-finished products from third party cost incurred due to lower than producing its own.